2001
DOI: 10.1364/josab.18.001443
|View full text |Cite
|
Sign up to set email alerts
|

Subsideband generation and modulational instability lasing in a fiber soliton laser

Abstract: We experimentally observed two forms of subsideband generation in the soliton spectrum of a passively modelocked fiber soliton ring laser. We found that the different forms of subsideband generation are related to the different strengths of the saturable absorption in the laser cavity. Analyzing featuring of the subsideband generations, we show that they are both modulational-instability lasings of the dispersive waves in the laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 31 publications
(46 reference statements)
2
15
0
Order By: Relevance
“…To this end we have extended the conventional Ginzburg-Landau equation model through incorporating the cavity features. In previous papers we have reported results of using the model in simulating the experimentally observed soliton sideband asymmetry [25], sub-sideband generation [26], twin-pulse soliton [27] and soliton pulse train non-uniformity [28]. We found that with the new model we could well reproduce all the experimentally observed phenomena of our laser.…”
Section: Theoretical Modelingmentioning
confidence: 52%
“…To this end we have extended the conventional Ginzburg-Landau equation model through incorporating the cavity features. In previous papers we have reported results of using the model in simulating the experimentally observed soliton sideband asymmetry [25], sub-sideband generation [26], twin-pulse soliton [27] and soliton pulse train non-uniformity [28]. We found that with the new model we could well reproduce all the experimentally observed phenomena of our laser.…”
Section: Theoretical Modelingmentioning
confidence: 52%
“…First, the secondary synchronous amplification gain profile in long wavelength band pumped by the first gain peak at 1530 nm of the erbium‐doped fiber is the main factor of sidebands asymmetry generation 56,57. In addition, the asymmetric sidebands are a consequence of the filtering effect caused by the fiber birefringence 58,59. Figure 5b is oscilloscope trace of mode‐locked pulse train, which shows that the pulse interval is 0.9 ns and the corresponding repetition rate is 1.1 GHz.…”
Section: Resultsmentioning
confidence: 99%
“…[56,57] In addition, the asymmetric sidebands are a consequence of the filtering effect caused by the fiber birefringence. [58,59] Figure 5b is oscilloscope trace of modelocked pulse train, which shows that the pulse interval is 0.9 ns and the corresponding repetition rate is 1.1 GHz. The mode-locked state at this time should be 229th harmonic mode-locking.…”
Section: Resultsmentioning
confidence: 99%
“…As the dispersive waves are continuous waves (CW), they are unstable for the modulation instability if their strength is strong enough. The subsideband generation in a fiber ring laser was first studied by Tang et al [12]. The subsidebands are the discrete spectral components beside the sidebands on the optical spectrum.…”
Section: Introductionmentioning
confidence: 99%